The Impact of Source of Information on Teenagers’ Knowledge of Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) - Herlina, Nina; Ekowati, Erik; Seftianingtyas, Woro Nurul; Nugroho, Widyo; Faqih, Alfida (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2024)
Background: The many cases of Human Immunodeficiency Virus (HIV)/Acquired Immuno Deficiency Syndrom (AIDS) in Indonesia within the age range of 25-49 years. Teenagers who are infected by HIV-AID in Indonesia shows an increasing number, misinformation and ignorance in teenagers are among the major causes of those increase. Teenagers are on a high risk since they have the tendency of involving in short term relationships with numerous partners. Therefore, to prevent further increase on the case, teenagers need to expand their source of informations and increase their knowledge n the matter. Researchers focused on studying the impact of source of informations towards the teenagers’ knowledge. Objective: to find out the co-relations between source of informations towards teenagers’ knowledge in a high school in in West Java. Method: Quantitative descriptive with cross sectional design. The number of samples taken are 99 respondents with purposive sampling technique and the statistic test using Chi Square test. Result: shows that there was significant correlations between the source of information on teenagers’ knowledge on HIV/AIDS with p-value 0,000. There is a significant impact between sources of information towards teenagers’ knowledge on HIV/AIDS. Conclusion: Increased knowledge on HIV-AID and understanding the steps on how to prevent the transmission became very important to encourage the teenagers to avoid getting infected by HIV/AIDS